ANALISIS PENGARUH KUALITAS PELAYANAN DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA BANDUNG CICADAS - Febriansyah, Angky (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2015)
Quality of service and knowledge of taxation is one of the factors that mayaffect taxpayer compliance, So expect good service quality and level of knowledge isalso good for the taxpayer compliance rate is increasing. The purpose of this study todetermine the effect of service quality and knowledge of taxation on individual taxpayercompliance in the tax office Cicadas Pratama Bandung.The method used in this research is descriptive method and verifikatif,Descriptive method used to determine the variable description quality of service andtaxation knowledge variables and variable individual taxpayer compliance whileverifikatif to determine the correlation between service quality and compliance of anindividual taxpayer and the correlation of knowledge of taxation and individual taxpayercompliance. To determine the effect of service quality and knowledge of taxation onindividual taxpayer compliance used statistical tests.Â The test statistic used is thecalculation of Person Product Moment correlation, coefficient of determination,hypothesis test using the software SPSS 15.0 for windows.The results of this study indicate that the quality of service and knowledge oftaxation have a significant effect in improving taxpayer compliance in individual taxoffice Pratama Bandung Cicadas. There is a correlations between service quality andknowledge of taxation with an individual taxpayer compliance in the tax office PratamaBandung Cicadas that is equal to 49.6%.